Hans Šlešs un viņa kolekcija - Rudzītis, Māris; Rudzīte, Mudīte; Komova, Jekaterina; Latvijas Universitātes Muzejs (My University, 2021)
Virtuālajā izstādē, kas veltīta malakologam Hansam Šlešam, Latvijas Universitātes Muzeja Zooloģijas kolekcijas piedāvā iespēju uzzināt par pētnieka biogrāfiju, publikācijām, zinātniskajiem sasniegumiem un Zooloģijas muzejam dāvināto gliemju čaulu paraugu kolekciju.

In a virtual exhibition dedicated to malacologist Hans Schlesch, the Zoological Collections of the Museum of the University of Latvia offers an opportunity to learn about the researcher's biography, publications, scientific achievements and the collection of mollusc shell samples donated to the Zoological Museum.
Hans Schlesch and his collection
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Hans Šlešs; malakoloģija; gliemji; zooloģija; Hans Schlesch; malacology; molluscs; zoology